DNA-based determination of suitable pollinating cultivars for the pear cultivar 'Carola' (Pyrus communis) - Nybom, H.; Sehic, J.; Mattisson, H. (International Journal of Horticultural Science, 2007)
Pollen-limited fruit set has long been suspected in some relatively low-yielding orchards with the Swedish pear cultivar 'Carola'. Fruit was therefore harvested on 23 'Carola' trees in a commercial pear orchard. The seeds were germinated and five seedlings from each tree were sampled to determine which of the surrounding cultivars had been the most successful pollinators. Leaves of 'Carola', the 7 putative pollinating cultivars and the 115 seedlings were analysed with 6 RAPD primers. By comparison of the band patterns, paternity could be ascertained for 74 seedlings. The by far most successful pollinator was 'Clara Frijs' which had sired approx. half of the seedlings, followed by 'Herzogin Elsa', `Skanskt Sockerpiiron', 'Alexandre Lucas', 'Coloree de Juillet' and 'Doyenne du Cornice'. The latter is the maternal parent of 'Carola', and these two cultivars must therefore share one S-allele and hence can only be semi-compatible. In addition, 6% of the seedlings were in all likelihood derived from selling_ since they showed no bands that did not occur also in 'Carola'. Maximum distance between 'Carola' trees and suitable pollinators should not exceed 15-20 tn. Longer distances may produce a serious dearth of compatible pollen as evidenced by the large percentage of seedlings derived either from selling. (25%) or from long-distance (> 40 m) pollen transfer (25%) when 'Carola' trees were surrounded by non-preferred pollinators.